Spontaneous quantitative processing in Chinese singular and plural picture naming: An event-related potentials analysis - Cui, Li-yan; Cheng, Wen-wen; Shan, Sha-rui; Lv, Wen; Sun, Chen-ming; Li, Run; Zhou, Shu; Chen, Zhuo-ming; Bao, Sheng-yong (Frontiers in Neuroscience, 2022)
Chinese nouns lack inflection and cannot reflect the quantitative relationship between singular and plural numbers. However, neural processes of picture naming are different from those of words, and we suspect that single and plural picture naming may involve quantitative processing. Therefore, Experiment 1 was designed by picking picture naming as the task and Chinese as the target language and compared the accuracy, reaction time, and event-related potentials (ERPs) between single and plural picture naming, where two types of pictures were mixed. Although the T-test showed no significant differences in behavioral data, there were differences in ERPs. ERP differences involved two components: P1 of 160-180 ms and P2 of 220-260 ms in the parietal-occipital lobe. These differences are suggested to reflect the neural differences in quantitative processing. Therefore, Chinese singular and plural picture naming consist of word production and implicit quantitative processing simultaneously. Based on singular and plural picture naming, a semantic factor (non-living vs. living items) was added in Experiment 2, and the observational indexes remained unchanged. There were no significant differences in behavioral data among the four conditions. After variance analysis, ERPs results indicated an interaction between semantic and quantitative processing in the central area at 180-280 ms. In summary, Chinese singular and plural picture naming includes two simultaneous neural processing tasks: word production and quantitative processing, which interact in the central area at 180-280 ms.